PENINGKATAN PERTUMBUHAN SEMAI NYATOH (Palaquium obtusifolium Burck) MELALUI PEMBERIAN BERBAGAI TAKARAN ABU JANJANG KELAPA SAWIT DI PERSAMAIAN - Lestari, Ayu; Wardah, Wardah; Wulandari, Retno; Rahmawati, Rahmawati (Jurnal Warta Rimba, 2020)
Nyatoh (palaqium obtusifolium Burck) is a type of tree that is also cultivated by the Indonesian community, however, until now, the use of good quality seedlings has been neglected so that the resulting stands have low productivity and quality. Therefore, efforts are needed to improve the quality of real seedlings by means of maintenance such as fertilization, watering and weeding.This research was conducted from January to April 2020 at the BPDASHL Palu-Poso Tadulako University association. This study used a completely randomized design with 5 treatments, each treatment was repeated 10 times. the treatment of the ash rate for oil palm basket, namely: A0 = soil without AJKS, A1 = soil + 5 g AJKS/Polybag, A2 = Soil + 10 g AJKS, A3 = soil + 15 g AJKS/Polybag and A4 = soil + 20 g AJKS /polybag. The parameters observed were the increase in seedling height growth, stem diameter, number of leaves and seedling firmness.The results of this study indicate that the provision of palm oil ash has a significant effect on the increase in the growth of the observed parameters. The best application of palm oil basket ash is 20 g/polybag with a soil weight of 1.5 kg/polybag. the average increase in height growth was 4.21 cm, diameter growth was 2.00 mm, the number of leaves was 2.50 and the growth of seedlings was 7.82.Keyword: AJKS, Nytahoh (Palaquium obtusifolium Burck)